2014
DOI: 10.1093/hmg/ddu041
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of loci associated with age at natural menopause in African-American women

Abstract: Age at menopause marks the end of a woman's reproductive life and its timing associates with risks for cancer, cardiovascular and bone disorders. GWAS and candidate gene studies conducted in women of European ancestry have identified 27 loci associated with age at menopause. The relevance of these loci to women of African ancestry has not been previously studied. We therefore sought to uncover additional menopause loci and investigate the relevance of European menopause loci by performing a GWAS meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 75 publications
1
42
0
Order By: Relevance
“…Recent genome-wide association studies (GWASs) among women of European ancestry have identified at least 106 genetic loci for AM (He et al 2009;Ong et al 2009;Perry et al 2009;Sulem et al 2009;Elks et al 2010;Perry et al 2014) and 21 loci for ANM (He et al 2009;Stolk et al 2009;Stolk et al 2012). However, only 24 AM loci and 9 ANM loci have been replicated in women of either Asian or African ancestry and no novel loci have been identified in these non-European populations (Liu et al 2009;Chen et al 2012;Shen et al 2013;Spencer et al 2013;Tanikawa et al 2013;Delahanty et al 2013;Carty et al 2013;Demerath et al 2013;Pyun et al 2014;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide association studies (GWASs) among women of European ancestry have identified at least 106 genetic loci for AM (He et al 2009;Ong et al 2009;Perry et al 2009;Sulem et al 2009;Elks et al 2010;Perry et al 2014) and 21 loci for ANM (He et al 2009;Stolk et al 2009;Stolk et al 2012). However, only 24 AM loci and 9 ANM loci have been replicated in women of either Asian or African ancestry and no novel loci have been identified in these non-European populations (Liu et al 2009;Chen et al 2012;Shen et al 2013;Spencer et al 2013;Tanikawa et al 2013;Delahanty et al 2013;Carty et al 2013;Demerath et al 2013;Pyun et al 2014;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The standard practice for checking and correcting pedigrees and relationships within genetic data sets is to use pairwise prediction programs, [14][15][16][17][18] such as RELPAIR 19 and PREST (Pedigree Relationship Statistical Test), 20 to verify that the level of relatedness between every pair of individuals falls close to the expected level of relatedness from the reported pedigree. [21][22][23][24][25][26][27][28] Although using pairwise estimates to check relationships in pedigrees is sometimes sufficient, there are four major drawbacks that we illustrate in this manuscript. First, pairwise checking will not catch pedigree errors if there are multiple pedigree structures that fit the genetic data and if the reported pedigree structure is among the incorrect possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to WGS to identify rare variants, genomewide association studies to assess common variation are increasingly large, available, and able to identify genetic loci associated with more quantitative traits such as the onset of puberty (153) and menopause (154)(155)(156)(157), thereby offering new insights in the genetic complexity of reproductive disorders. Importantly, few loci associated with the age of menarche were mapped close to known IGD genes, and most genome-wide associations are either 1) localized at some distance from coding regions revealing possible long-range DNA interactions; 2) interrupt transcription factor binding with possible effects on downstream targets; or 3) interrupt noncoding RNA, which may play a role in the regulation of transcription and translation of target genes (158,159).…”
Section: A New Tools and Approaches For The Discovery Of Igd Genesmentioning
confidence: 99%